1967
DOI: 10.1037/h0024997
|View full text |Cite
|
Sign up to set email alerts
|

Opening offer and frequency of concession as bargaining strategies.

Abstract: The experiment was allegedly a simulated bargaining session between a buyer and a seller, who communicated via written offers. Actually, the E substituted standardized bargaining patterns for the offers of both opponents, and conducted simultaneous bargaining sessions with each of the Ss. In a factorial design, the type of initial offer, extreme or moderate, the frequency of concession, moderate or infrequent, and the S's role, buyer or seller, were varied. The major findings were: (a) Sellers did better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
2
2

Year Published

1972
1972
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 1 publication
2
79
2
2
Order By: Relevance
“…Our research extends numerous earlier findings concerning the impact of initial offers on the distributive aspect of negotiation (Chertkoff and Conley, 1967;Liebert et al, 1968;Benton et al, 1972;Yukl, 1974;Rubin and Brown, 1975;Raiffa, 1982), by showing the impact of opening offers on the integrative aspect of negotiation as well. In particular, while earlier research has repeatedly suggested that the overall value of an initial-offer may serve as an anchor (Polzer and Neale, 1995;Northcraft and Neale, 1987;Ritov, 1996;De Dreu et al, 1999;Galinsky and Mussweiler, in press), the present research uncovers the potential role of the initial offer in establishing with in-issue anchors.…”
Section: Discussionmentioning
confidence: 51%
“…Our research extends numerous earlier findings concerning the impact of initial offers on the distributive aspect of negotiation (Chertkoff and Conley, 1967;Liebert et al, 1968;Benton et al, 1972;Yukl, 1974;Rubin and Brown, 1975;Raiffa, 1982), by showing the impact of opening offers on the integrative aspect of negotiation as well. In particular, while earlier research has repeatedly suggested that the overall value of an initial-offer may serve as an anchor (Polzer and Neale, 1995;Northcraft and Neale, 1987;Ritov, 1996;De Dreu et al, 1999;Galinsky and Mussweiler, in press), the present research uncovers the potential role of the initial offer in establishing with in-issue anchors.…”
Section: Discussionmentioning
confidence: 51%
“…The reciprocal concessions rule states that "You should make concessions to those who make concessions to you" (Cialdini et al, 1975, p. 206). Cialdini et al cited evidence from the reciprocity (Gouldner, 1960) and bargaining literature (Chertkoff & Conley, 1967;Benton, Kelley, & Liebling, 1972) and concluded that the offer of a small favour or a concession by one participant increases the likelihood that the other participant will return the favour or make a similar concession. In a series of three experiments, Cialdini et al showed that it is indeed an effective strategy to make an unreasonably large request and follow it with a much smaller one.…”
mentioning
confidence: 99%
“…In another experimental condition, the participants asked for a very high price and gradually lowered the price throughout the negotiation. Komorita and Brenner concluded that failing to make a concession in a negotiation, even if the first starting price is fair, is an ineffective strategy for reaching an agreement (see also Chertkoff & Conley, 1967). Advocates of the reciprocal concessions explanation for DITF argue that the process is similar.…”
Section: Reciprocal Concessionsmentioning
confidence: 99%